2018
DOI: 10.9734/jalsi/2018/43813
|View full text |Cite
|
Sign up to set email alerts
|

Gliricidia Leaf Meal in Broiler Chickens Diet: Effects on Performance, Carcass, and Haemato-biochemical Parameters

Abstract: Aims: This study seeks to access the influence of Gliricidia leaf meal on broiler chickens’ growth performance, carcass traits, and haemato-biochemical parameters. Study Design:  Completely randomised design. Place and Duration of Study: The 56-day feeding trial was carried out at the Teaching and Research Farm of Agricultural Technology Department, The Federal Polytechnic, Ado Ekiti, Nigeria. Methodology:  Fresh Gliricidia sepium leaves were harvested, shade dried and milled to produce leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, the increase in WBC counts (still within the normal ranges) indicates a better ability to against infections disease (Olumide et al, 2018;Adedeji et al, 2019), which is seen in the birds fed diets with 1 and 2% atung seed powder. This result is comparable with some previous studies of Oleforuh-Okoleh et al (2015), Oloruntola (2018), Olumide et al (2018), andAnsari et al (2012), who reported that inclusion phytobiotic additives of garlic water extract, Glisiridia leaf meal, Ocimum gratissimum leaf meal, and A. indica leaf meal, respectively, increased WBC numbers significantly in broiler chickens. The WBC counts of birds in the control group were lowest, which could be assumed that these birds have less ability to defend against infection disease when compared to the other groups.…”
Section: Haematological Parameterssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, the increase in WBC counts (still within the normal ranges) indicates a better ability to against infections disease (Olumide et al, 2018;Adedeji et al, 2019), which is seen in the birds fed diets with 1 and 2% atung seed powder. This result is comparable with some previous studies of Oleforuh-Okoleh et al (2015), Oloruntola (2018), Olumide et al (2018), andAnsari et al (2012), who reported that inclusion phytobiotic additives of garlic water extract, Glisiridia leaf meal, Ocimum gratissimum leaf meal, and A. indica leaf meal, respectively, increased WBC numbers significantly in broiler chickens. The WBC counts of birds in the control group were lowest, which could be assumed that these birds have less ability to defend against infection disease when compared to the other groups.…”
Section: Haematological Parameterssupporting
confidence: 92%
“…The presence of tannins in high amounts in the nonruminants feed could be decreased feed intake, which was in agreement with the studies by Biswas and Wakita (2001) and Sarker et al (2010). In addition, several studies by Khalaji et al (2018), Olumide et al (2018), andOloruntola (2018) have found that high doses in the inclusion of phytobiotic additives of Camellia L extract, Ocimum gratissimum, and glyciridia leaf meal, respectively, reduced feed intake and weight gain of broiler chickens. Oloruntola (2018) suggested that phytobiotic inclusion at high doses could be impaired the palatability of feed caused by antinutritional factors was contained in the plant origin.…”
Section: Growth Performancementioning
confidence: 96%
See 1 more Smart Citation